Diversity and spatial and temporal variation of benthic macroinvertebrates with respect to the trophic state of Lake Figueira in the South of Brazil - Lima,Fernanda Blauth de (2013)
Benthic macroinvertebrates are widely used in evaluations of environmental impact and recommended in biomonitoring, but little used in Brazilian lentic environments. One of the main objectives has been to explain and predict the distribution of those species according to environmental characteristics. Thus, the study aims to characterize the predominant fauna of the Lake Figueira sediment and its relationship with organic matter and depth, analyzing seasonal variation in communities and aiming to select bioindicators of the trophic state. Sampling was carried out from January 2008 to January 2009, along the lagoon fetch, with an Ekmann-Birge dredge (area 225 cm²). Taxon richness was not significantly related with depth and organic matter content, but those variables were highly correlated (r = 0.962; r² = 0.926 and p < 0.001). The constant oxygenation of the whole water column allows the occurrence of organisms, independent of depth and organic matter content. Chironomidae was the most abundant taxon and from the frequency of occurrence, abundance and clustering analysis it was possible to select Larsia sp. , Goeldichironomus maculatus, Xenochironomus sp. , Aedokritus sp. Cladopelma forcipis, Cryptochironomus brasiliensis, Nilothauma sp.1 and Caladomyia sp. C, Tanytarsus sp. , Tanytarsus rhabdomantis and Chironomus gr. salinarius as potential indicators related with the spatiotemporal faunal distribution of Lake Figueira.